CHARACTERISTICS OF PARONYMS IN THE UZBEK LANGUAGE - Yusupova Soxiba Islombek qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract. This article examines the linguistic characteristics of paronyms in the Uzbek language, focusing on their phonetic similarity and semantic distinctions. The study analyzes the formation, classification, and functional features of paronyms, as well as their role in oral and written communication. Particular attention is paid to the causes of confusion between paronyms and the types of lexical and stylistic errors that arise  from  their  incorrect  usage.  Through  descriptive  and  comparative  analysis, examples of paronymic word pairs are explored to illustrate their usage in different communicative  contexts.  The  findings  of  the  study  contribute  to  a  clearer understanding  of  paronymy  in  Uzbek  linguistics  and  highlight  its  importance  in improving speech culture and language competence.